ICONIC SYMBOLS IN THE DECOR OF TRADITIONAL VESTS OF THE COLLECTION OF THE NATIONAL MUSEUM OF ETNOGRAPHY AND NATURAL HISTORY OF THE REPUBLIC OF MOLDOVA - Bizgu, T. (Art and Design, 2023)
Purpose: the study of signs and symbols in the decoration of vests included in the collection of the Chisinau National Museum of Ethnography and Natural History (NMENH). Methodology. Visual-analytical, morphological, artistic-compositional method and thematic and comparative analysis were applied. Results. As a result of the analysis of museum's collection of vests from the NMENH of the Republic of Moldova and the inventory description for each exhibit, it was found that the museum purchased vests from Moldova, as well as from Romania, Bulgaria, Gagauzia. The paper offers a wide range of special terminology related to the vest of Romania, Moldova and Ukraine. The scientific novelty. As a result of this work, the analysis of decorative elements was carried out for the first time and the iconic symbolism of this collection of vests was characterized. A gallery with the most remarkable exhibits will help to reveal the area under study. Practical significance. Over the last decade, there has been a growing interest in traditional shirts, which, according to the author, will soon require in-depth information about traditional vests. The study of signs, symbols, color palettes that come from the depths of our roots are important for the present and future generations, as they reveal the depth and sophistication of the spiritual development of our ancestors. The study of the characteristics of the traditional vest is necessary to save this treasure and use it as a bright source of inspiration for creating modern collections, for researchers, scientists, ethnologists, etc.